Rent : Rent Collection Yard (Beijing - Lucerne : Galerie Urs Meile, 2008)
Beuys, Joseph ; Cai, Guo-Qiang ; Colonnello, Nataline ; Dai, Shenghong ; Fan, Di'an ; Leister, Christiane ; Li, Xianting ; Li, Zhanyang ; Lin, Suling ; Lu, Ronggzhi ; Lu, Qing ; Sigg, Uli ; Sui, Jianguo ; Szeemann, Harald ; Tang, Xin ; Wang, Xiaojian ; Wang, Xingwei ; Gao, Minglu ; Gu, Zhenqing ; He, Yunchang ; Gnos, Livia ; Huang, Liaoyuan ; Keller, Samuel ; Man, Man ; Mao, Ran ; Mao, Zedong ; Meilr, Urs ; Qin, Ga ; Qiu, Zhjir ; Xiang, Jing ; Ye, Yongqing ; Yu, Ke ; Zhang, Guanghua ; Zhang, Huan ; Chang, Johnson
Li Zhanyang, Rent - Rent Collection Yard, Galerie Urs Leile, Beijing-Lucerne, Beijing, China, April 26 - August 24, 2008
boek
Keywords: Li Zhanyang; Ai, Weiwei